Business Development Strategy for Muslimah Female UMKM Person of Songket Fabric in Batu Bara Using the Triple Helix Method - Muhammad Arif; Yenni Samri Juliati Nst; Muhammad Alqodri Pratama (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to determine how the strategies used by Muslim women who do UMKM songket Batubara in developing their businesses. The sample used in this study were four MSME actors of songket Batubara, and the approach used was an inductive qualitative approach. In this study, the data analysis tools used were SWOT analysis (Strength, Weakness, Opportunities, and Threats). The results of the analysis show that this study produces a triple helix stakeholder model in this study as: a. Academics in this case are a source of knowledge with the latest theories and are relevant to the business developed by Batu Bara songket business actors run by Muslim women in Batu Bara to gain a competitive and sustainable advantage. b. Business is an entity that carries out business processes in creating added value and maintaining sustainable growth. c. The government acts as a regulator as well as a controller that has regulations and responsibilities in developing businesses. The government also has a role to coordinate stakeholders who contribute to the development of women's businesses in the treatment of Batu Bara songket cloth. Based on the results of the SWOT analysis, it can be seen that the Stakeholders are implementing the SO (Strength and Opportunities) strategy, which is a strategy in which the company uses the strengths and opportunities it has to run its business.